2021
DOI: 10.1002/er.7250
|View full text |Cite
|
Sign up to set email alerts
|

Performance indices optimization of l ong‐lived fission products transmutation in fast reactors

Abstract: Summary An investigation on the nuclear transmutations of elemental long‐lived fission products (LLFPs) in a fast reactor is being conducted in Japan, focusing on the Se‐79, Zr‐93, Tc‐99, Pd‐107, I‐129, and Cs‐135, to reduce the environmental burden. With their high neutron flux and adequate excessive neutrons, fast reactors are considered strong candidates for transmuting those LLFPs into stable isotopes or shorter effective half‐lives under the partition and transmutation (P/T) strategy. In this investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…As mentioned above, six radionuclides 79 Se, 93 Zr, 99 Tc, 107 Pd, 129 I and 135 Cs are selected as transmutation candidates. These LLFPs nuclides were mixed with the neutron moderator (70 at% LLFPs + 30 at% YD 2 ) and were loaded into the LLFPs assemblies to improve the transmutation performance since the feasibility of this moderator has been proven 9 , 11 , 29 . The moderator could soften the neutron at the LLFPs assembly region while having little effect on the neutron energy spectrum of the entire core, as it is loaded in the radial blanket region with a small loading mass.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned above, six radionuclides 79 Se, 93 Zr, 99 Tc, 107 Pd, 129 I and 135 Cs are selected as transmutation candidates. These LLFPs nuclides were mixed with the neutron moderator (70 at% LLFPs + 30 at% YD 2 ) and were loaded into the LLFPs assemblies to improve the transmutation performance since the feasibility of this moderator has been proven 9 , 11 , 29 . The moderator could soften the neutron at the LLFPs assembly region while having little effect on the neutron energy spectrum of the entire core, as it is loaded in the radial blanket region with a small loading mass.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has revealed that both ADS and solid fuel critical fast reactors face technical challenges in transmuting TRUs to achieve a high transmutation rate (transmutation amount per unit time) within an accepted transmutation time. 13 First, in consideration of core critical and reactivity control, a transmutation system is equipped with fertile material in addition to the TRUs, and thus it is necessary to increase the TRUs loading and reduce the fertile material loading to enhance the transmutation rate. Meanwhile, a nuclide (e.g., thorium) with a relatively low TRUs yield should be chosen as the fertile material.…”
Section: Introductionmentioning
confidence: 99%